The limits of natural law: liability for wrongdoing in the Inleidinge - Sampson, J (Brill Academic Publishers, 2019)
This article focuses on Grotius’s treatment of obligations arising from wrongdoing in his Inleidinge. The work has clear parallels with the natural law formulation of the same topic in De Jure Belli ac Pacis, and this article explores the extent of the similarities. It focuses on points of divergence, suggesting that the theoretical coherence of the natural law approach to obligations arising from wrongdoing was challenged primarily by extant legislative enactments. These provided either for region-specific doctrines, or rules that proved difficult to reconcile with the underlying principles of natural law, especially the primacy of fault. While much of the Inleidinge’s treatment of liability arising from wrongdoing is consonant with Grotius’ approach to the topic in De Jure Belli ac Pacis, these discrete points of dissimilarity serve as a reminder of the limits of theoretical accounts of private law.